A Study on Factors for Travel Time Variability in Dhaka City Corporation Area - Anwar, A H M Mehbub (Journal of Bangladesh Institute of Planners, 2010)
Knowledge of travel time variability is valuable for improving the reliability of traffic information services and increasing the accuracy of travel time predictions. The paper attempts to explore the travel time variability in Dhaka city with the data collected by the probe vehicle. A comprehensive investigation of travel time distribution was conducted in terms of various time windows. With respect to travel time variability, approximately each mean travel time level has a certain variability associated with it. It has been observed that the higher travel times in the morning off-peak and afternoon peak have the lower coefficient of variance but the smaller mean travel time in the morning peak has the higher variability than other times of the day. The travel time variability has also been investigated by multiplicative nonlinear regression model. To establish the model, delay time (delay), volume-capacity (V/C) ratio and congestion index (CI), which is actual travel time divided by free flow time, were considered as explanatory variables while logarithm of travel time was used as dependent variable. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 53-64